1996
DOI: 10.1215/03616878-21-2-315
|View full text |Cite
|
Sign up to set email alerts
|

Medical Malpractice in Michigan: An Economic Analysis

Abstract: We analyzed the factors determining the amount of the recovery on claims based on medical malpractice. Our data set, which previously was not explored, consists of 20,428 claims arising within Michigan that were closed between 1978 and 1990. During this period, major changes were made in the law governing malpractice litigation. We determine the effect of these changes and of various other factors affecting medical malpractice claims. We analyze the effect of a statute that was designed to curtail "forum shopp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…New York may be different from other states. However, two Michigan studies have also found some evidence of in‐state variation (Southwick & Young 1992; Spurr & Simmons 1996).…”
Section: Discussion Of Results and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…New York may be different from other states. However, two Michigan studies have also found some evidence of in‐state variation (Southwick & Young 1992; Spurr & Simmons 1996).…”
Section: Discussion Of Results and Limitationsmentioning
confidence: 99%
“…Nor did they look for evidence that variations were durable over time. A later study by Spurr and Simmons (1996) looked only at a single Michigan county. It found that Wayne County's share of the state's malpractice claims (46.5–43.1 percent) was nearly twice as large as its share of the state's population (25.2–22.7 percent).…”
Section: Introductionmentioning
confidence: 99%
“…Forum Shopping is a practice whereby plaintiff's lawyers contrived various pretexts to file claims in counties where damage awards tend to be higher, such as the Wayne County, Detroit metropolitan area(Spurr and Simmons 1996).REVIEW OF SOCIAL ECONOMY…”
mentioning
confidence: 99%